Microsatellites and petal morphology reveal new patterns of admixture in Orchis hybrid zones. Issue 8 (21st August 2021) - Bersweden, Leif; Viruel, Juan; Schatz, Bertrand; Harland, Joanna; Gargiulo, Roberta; Cowan, Robyn S.; Calevo, Jacopo; Juan, Ana; Clarkson, James J.; Leitch, Andrew R.; Fay, Michael F.
Abstract: Premise: The genetic structure of hybrid zones provides insight into the potential for gene flow to occur between plant taxa. Four closely related European orchid species ( Orchis anthropophora, O. militaris, O. purpurea, and O. simia ) hybridize when they co‐occur. We aimed to characterize patterns of hybridization in O. militaris–O. purpurea, O. purpurea–O. simia, and O. anthropophora–O. simia hybrid zones using molecular and morphological data. Methods: We used 11 newly isolated nuclear microsatellites to genotype 695 individuals collected from seven hybrid zones and six allopatric parental populations in France. Geometric morphometric analysis was conducted using 15 labellum landmarks to capture the main aspects of petal shape. Results: Backcrossing was asymmetric toward O. militaris in multiple O. militaris–O. purpurea hybrid zones. Hybrids in O. purpurea–O. simia and O. anthropophora–O. simia hybrid zones were largely limited to F1 and F2 generations, but further admixture had occurred. These patterns were reflected in labellum geometric morphometric data, which correlated strongly with nuclear microsatellite data in all three species combinations. Conclusions: The coexistence of parental and admixed individuals in these Orchis hybrid zones implies they are likely to be tension zones being maintained by a balance between gene flow into the hybrid zone and selection acting against admixed individuals. The pattern of admixture in the three species combinations suggests intrinsic selection acting on the hybrids is weaker in more closely related taxa.